Corporate social responsibility (CSR) practice, disclosure and public awareness : a case study of Lembaga Tabung Haji in Malaysia - Mohd Hakimi bin Harman (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
This paper studies the Corporate Social Responsibility (CSR) practices and disclosure by Lembaga Tabung Haji in Malaysia while at the same time measuring the public awareness on the CSR activities conducted by the institution. The paper adopts the combination of quantitative and qualitative descriptive methods whereby the data was collected and gathered from three (3) different sources, annual reports, e-mail interview and questionnaire. The findings suggested that Lembaga Tabung Haji conducted various CSR activities and it has been reported in the annual reports starting from 2005. Regardless of the CSR activities being disclosed in the annual reports, the report does not have any standard format whereby it differs from year to year and only with minimal coverage. However, the coverage has increased from year to year with only 1 page in 2005 to 17 pages in 2012 and with only 3 activities in 2005 to 17 activities in 2012. With regards to awareness, the level of awareness of the public is very low whereby most of the respondents do not really aware about the CSR activities conducted by Lembaga Tabung Haji and the highest level of awareness was at the workplace. Several limitations of the study were the lack of cooperation from the person in charge of Lembaga Tabung Haji's group CSR and no respondents from Lembaga Tabung Haji's staff. It is suggested for the future research to analyze the impacts of Lembaga Tabung Haji's CSR activities towards the economic developments of the Ummah and also to study the best CSR program that could benefit the majority of the society.